2015
DOI: 10.1098/rsbl.2015.0339
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and extinction of the ichthyosaurs from the perspective of quantitative ecospace modelling

Abstract: The role of niche specialization and narrowing in the evolution and extinction of the ichthyosaurs has been widely discussed in the literature. However, previous studies have concentrated on a qualitative discussion of these variables only. Here, we use the recently developed approach of quantitative ecospace modelling to provide a high-resolution quantitative examination of the changes in dietary and ecological niche experienced by the ichthyosaurs throughout their evolution in the Mesozoic. In particular, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 16 publications
1
41
4
Order By: Relevance
“…This grade may be divided into two subgrades: the earlier, Middle Triassic Cymbospondylus-Mixosaurus group, and the Middle-Late Triassic Shastasaurus-Shonisaurus group. The former group includes taxa that represent the early ecological diversification of ichthyosaurs, with a broad range of body forms habits, associated with an increase in disparity (Massare 1987;Thorne et al 2011;Fröbisch et al 2013;Dick & Maxwell 2015). This is marked in the above phylogeny by character changes related to the teeth as a potential synapomorphy of Mixosauridae (e.g.…”
Section: Discussion Ichthyosaur Evolution: Clades and Gradesmentioning
confidence: 99%
“…This grade may be divided into two subgrades: the earlier, Middle Triassic Cymbospondylus-Mixosaurus group, and the Middle-Late Triassic Shastasaurus-Shonisaurus group. The former group includes taxa that represent the early ecological diversification of ichthyosaurs, with a broad range of body forms habits, associated with an increase in disparity (Massare 1987;Thorne et al 2011;Fröbisch et al 2013;Dick & Maxwell 2015). This is marked in the above phylogeny by character changes related to the teeth as a potential synapomorphy of Mixosauridae (e.g.…”
Section: Discussion Ichthyosaur Evolution: Clades and Gradesmentioning
confidence: 99%
“…The mass extinction was preceded by a period of extreme climate changes (Friedrich et al 2012)-possibly weakening ecosystems before the final extinction. The extinction of the dinosaurs is therefore an excellent test case of whether lowered ecosystem resilience can catalyze major extinction events, as has been suggested for other mass extinctions (Roopnarine et al 2007;Dick and Maxwell 2015). The lead-up to the extinction of the dinosaurs is of added interest, because it has been suggested that dinosaurs showed a broad-scale global decline in speciation rates through the last 40 Myr of the Cretaceous (Sakamoto et al 2016), challenging the general consensus that there A B C FIGURE 1.…”
Section: Introductionmentioning
confidence: 99%
“…species' intrinsic characteristics that directly influence their ecological role 32 ). The few studies that have used this or similar approaches have focused specifically on the ecological consequences of the extinction of invertebrates 24,[33][34][35] (but see 37 ). These organisms have important ecological roles, but are usually small-sized, occupy low trophic levels, and tend to be highly speciose.…”
mentioning
confidence: 99%